A Regionally Evolving Transpressional Duplex Along the Northern Margin of the Altyn Tagh Fault: New Kinematic and Timing Constraints From the Sanweishan and Nanjieshan, China. Issue 2 (23rd February 2020) - Yang, Haibo; Yang, Xiaoping; Cunningham, Dickson; Hu, Zongkai; Huang, Xiongnan; Huang, Weiliang; Yang, Huili; Miao, Shuqing; Zhang, Ling
Abstract: In this study, we document the kinematics and Late Quaternary slip rates of actively developing faults and folds on the northern side of the Altyn Tagh Fault (ATF) that accommodate uplift and lateral expansion of the northern Tibetan Plateau. Field observations and detailed measurements using Unmanned‐Aerial‐Vehicle Structure‐from‐Motion high‐resolution imagery of offset fan surfaces, gullies, and channel risers coupled with optically stimulated luminescence and 10 Be ages constrain the timing and slip rates of the Sanweishan Fault (SWSF) and Nanjieshan Fault (NJSF) systems. The NE striking SWSF is characterized by sinistral strike slip with a top‐to‐the‐NW thrusting component. Offset geomorphic markers and dating results yield Pleistocene strike slip and vertical uplift rates of 0.06–1.25 mm/a and 0.05–0.08 mm/a, respectively. The E‐W trending NJSF is dominated by north and south directed thrusting and km‐scale folding with variable components of sinistral strike slip. The calculated total N‐S shortening rate across the NJSF is ~0.3 mm/a. Low rates of deformation for the SWSF and NJSF account for less than 10% of the total intraplate strain accommodated along the northeasternmost ATF system. Over a 1, 000‐km length, the northward expansion of the Tibetan Plateau occurs by progressive northeastward growth of a transpressional duplex rooted SE into the ATF. An assumed crustal strength discontinuity along the northeast trending southern margin of the Tarim Craton focuses oblique convergence along the ATF. Oblique‐slip thrusting and sinistral strike slip along the ATF and to the north accommodate the oblique convergence, consistent with the ENE directed geodetically derived crustal velocity field driven by India's continued indentation 1, 500 km to the south. Key Points: Kinematics and slip rates of the Sanweishan and Nanjieshan Fault systems directly north of the Altyn Tagh Fault (ATF) are newly constrained The north side of the ATF is a regionally evolving transpressional duplex accommodating Tibetan Plateau expansion into the Tarim Craton Slowly deforming faults of the Sanweishan and Nanjieshan may present an underappreciated seismic hazard for Silk Road Corridor cities